Comportamento mecânico do concreto de alta resistência reforçado com fibras - Almeida, Ricardo Laguardia Justen de (2023)
The addition of fibers to concrete provides ductility and their contribution to high-strength concrete may be even more relevant due to the high brittleness of the material. Nevertheless, research in the literature investigating the mechanical behavior of high- strength fiber-reinforced concrete (HSFRC) is limited and mostly involves concrete reinforced with steel fibers. This research investigated the mechanical behavior of high-strength fiber-reinforced concrete (HSFRC) through an extensive experimental program with six different types of fiber divided into three categories according to the material of the fiber: hooked-end steel fiber, crimped steel fiber, chopped glass fiber, pultruded glass fiber, monofilament polymeric fiber and twisted polymeric fiber. Each one of these fibers was studied at three different volume fractions (Vf) (0.50%, 0.75% and 1.00%), making a total of 29 different mixes in the experimental program. The parameters analyzed were the type and fiber content and the compressive strength of the concrete (60 and 90 MPa). The mechanical behavior was investigated through compressive displacement-controlled tests to obtain the complete stress-strain curve and three-point bending tests in notched beams to determine the residual strengths. The test results showed that the addition of fibers can affect the mechanical properties of concrete, such as compressive strength, elastic modulus and peak strain, depending on the type and fiber content. Toughness, on the other hand, is clearly influenced by the fiber addition and content. In general, the greater the fiber content, the greater the toughness and residual strength in bending regardless of the fiber type. Steel fibers provided the highest toughness and residual strengths in compression, followed by glass fibers and polymeric fibers. Constitutive models in compression were proposed for each type of fiber and showed good agreement with the experimental results and can be used to estimate the ductility and toughness of the HSFRC. In bending, the limit of proportionality is slightly influenced by the fiber content and hooked-end steel fibers also provided the highest residual strengths, followed by pultruded glass fibers and crimped steel fibers, polymeric fibers and chopped glass fibers. Furthermore, the requirements of technical standards for using fibers in structural applications were discussed and must be reviewed for high-strength fiber-reinforced concrete. The experimental results of the bending tests were used in finite element modelling (FEM) to obtain the constitutive model in tension by inverse analysis. The results obtained with the numerical model showed good agreement with the experimental results in terms of toughness and proved to be a useful tool for numerical simulations of fiber- reinforced concrete. From the validation of the numerical model, multilinear constitutive models were proposed and can be used for design purposes. The analyzes carried out also demonstrated that the simplified models of the technical standard can overestimate (in the case of the linear model) or underestimate (in the case of the rigid-plastic model) the toughness of HSFRC and do not represent the post-cracking behavior of high-strength concrete reinforced with glass and polymeric fibers.